Multilayer Flexible Metamaterials With Fano Resonances - Zhaoxin Geng; Yueyue Wang; Yapeng Cao; Hongda Chen (IEEE Photonics Journal, 2016)
A set of multilayer flexible metamaterials (MMs), which consist of three layers of parylene C films and three layers of gold split ring resonators (SRRs), was designed and fabricated. The transmission spectra of these MMs were measured in the terahertz (THz) region. Additionally, the structures of SRRs on each layer were changed from symmetric to asymmetric to investigate Fano resonances shown in these MMs. Meanwhile, by changing the thickness of each layer of parylene C, the coupling between different layers and the corresponding spectra change were explored. The results show that increased layers of MMs support new resonant modes and lead to Fano resonances with narrow linewidths in spectra. Therefore, this kind of multilayer flexible MM has potential applications in the THz biomolecule sensing field.